2018
DOI: 10.1002/ijch.201800041
|View full text |Cite
|
Sign up to set email alerts
|

Pillar[5]arene‐stabilized Plasmonic Nanoparticles as Selective SERS Sensors

Abstract: We present here a simple procedure for the surface modification of plasmonic nanoparticles (NPs) with a cationic water-soluble ammonium pillar[5]arene (AP[5]A) in order to create selective surface-enhanced Raman scattering (SERS) spectroscopy based sensors. The strategy is based on a ligand exchange reaction between the AP[5]A and the stabilizing agent of the as-prepared plasmonic NPs. The approach could be applied to plasmonic nanoparticles either negatively charged, stabilized by citrate ions (Au spheres) or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…The obtained LOD was found to be lower than previously reported detection limit achieved using SERS and non‐SERS based pyocyanin detection platforms [39,49,51] . For example, the detection limit of electrochemical sensor designed using palladium hydride electrode by Webster et al.…”
Section: Resultsmentioning
confidence: 61%
“…The obtained LOD was found to be lower than previously reported detection limit achieved using SERS and non‐SERS based pyocyanin detection platforms [39,49,51] . For example, the detection limit of electrochemical sensor designed using palladium hydride electrode by Webster et al.…”
Section: Resultsmentioning
confidence: 61%
“…One may infer that signal enhancement for analytes can be obtained by tailoring the size and shape of the nanoparticles [12][13][14], in addition to the conformation of the analyte adsorbed as in the detection of B-complex vitamins in pharmaceutical samples [15].Such control in nanoparticle shape is afforded through various synthetic routes [16][17][18], then allowing the Localized Surface Plasmon Resonances (LSPR) to be tuned according to the region of best response (excitation) of the analyte [14,18,19]. For example, the near electromagnetic field is higher in nanoprisms (AgNPR), nanostars (AgNS) and nanorods (AgNR) than on spherical nanoparticles (AgNP) [18,19], and the LSPR may be wider to allow excitation down to the near infrared (IR) [18][19][20]. Indeed, Rycenga et al [21] reported higher SERS activity for three molecules adsorbed on Ag nanocubes (AgNC) than on AgNP due to the wider LSPR for AgNC.…”
mentioning
confidence: 99%